Nature(s) Revisited: Identities and Indigenous Peoples (Fourth World Journal, 2010)
This article explores the complex relationships between Indigenous identities, nature, capitalism, and global influences. It critiques Western constructions of nature and calls for recognizing multiple ‘natures’ connected to diverse Indigenous identities. The article addresses the challenges Indigenous communities face in negotiating their identities within capitalist systems and emphasizes the importance of inclusive approaches to environmental stewardship. It also examines the interactions between international Indigenous elites and local Indigenous groups, highlighting how global actors influence the construction of local identities. Themes include Indigenous environmental activism, ecofeminism, and critiques of domination over nature. Overall, the article offers a nuanced understanding of the interplay between culture, nature, and global capitalism from Indigenous perspectives.